Asymptotics of regular convolution quotients - Bogoljub Stankovic (International Journal of Mathematics and Mathematical Sciences)
The asymptotic behaviour of a class of generalized functions, named regular convolution quotients, has been defined and analysed. Some properties of such asymptotics, which can be useful in applications, have been proved.